Loop underlay tympanoplasty for anterior, subtotal and total tympanic membrane perforations: a retrospective review - Rana Barake; Tamer El Natout; Marc Bassim; Mohammad Ali El Natout (Journal of Otolaryngology - Head and Neck Surgery)
Abstract Background The study aims at reporting our experience with loop underlay tympanoplasty, a modification of the underlay technique previously reported, for the reconstruction of anterior, subtotal or total tympanic membrane perforations. Methods A retrospective review of charts of patients who have undergone loop underlay tympanoplasty from January 2002 to January 2012 was performed. One thousand one hundred patients were included. Hearing test results preoperatively and postoperatively were reported. On follow up visits, the closure of the tympanic membrane perforation and the improvement of hearing compared to preoperative measurements with absence of complications were considered as successful outcomes of the surgery. Results At the three-month follow-up visit, the perforation closure rate was found to be 99.3% and Air-Bone Gap closure rate to less than 10 dB was 99.5%. The complication rate, including post-operative infection, was 0.72%. Conclusion The loop underlay technique combines advantages of both underlay and overlay techniques with excellent postoperative outcomes.